Leverage points for improving urban biodiversity conservation in the Anthropocene: A novel ecosystem lens for social-ecological transformation - Collier, Marcus (My University, 2024)
Environmental governance faces persistent challenges worldwide, with traditional conservation and restoration policies often proving ineffective against ongoing environmental degradation and biodiversity loss. This is driven largely by complex regulatory procedures and an outdated understanding of ecosystem dynamics and change which often fail to effectively engage stakeholders or acknowledge the emergence and value of disturbed or novel ecosystems. This paper advocates for a paradigm shift in conventional environmental policy in the Global North to embrace ecological novelty and reevaluate conservation strategies, particularly within urban contexts. Drawing on case studies from Ireland, Australia, and the United States, it examines existing environmental legislation and identifies critical leverage points for transformative change utilizing a systems thinking and multispecies justice perspective. The findings highlight cross-cutting themes, similarities and differences across regions. We conclude with recommendations for alternative approaches to biodiversity conservation that ac- count for the global redistribution of species and the prevalence of novel ecosystems. This may enable policy- makers, practitioners and other stakeholders to envision more flexible, nimble, and adaptive policy frameworks that strive toward mutual flourishing and address the evolving challenges of the Anthropocene.
Keywords: Urban planning; Novel ecosystems, Wild spaces, Environmental policies, Systems thinking, Anthropocene; Inclusive Society; Smart & Sustainable Planet; Anthropocene; Biodiversity; Ecology; Environmental planning and sustainable development; NOVEL ECOSYSTEMS; Urban Geography; Community; Environment and housing; Social participation